2016
DOI: 10.14742/ajet.2232
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating meaningful gamification in a blended learning research methods class: Examining student learning, engagement, and affective outcomes

Abstract: <p>In this study, we investigated how the use of meaningful gamification affects student learning, engagement, and affective outcomes in a short, 3-day blended learning research methods class using a combination of experimental and qualitative research methods. Twenty-two postgraduates were randomly split into two groups taught by the same instructor. The experimental group attended a course that incorporated the notion of meaningful gamification – that is, utilising the game mechanics of points, badges,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(73 citation statements)
references
References 32 publications
3
55
0
4
Order By: Relevance
“…For the purpose of this study, following Kuh (2009), engagement is considered to represent -the time and effort students devote to activities that are empirically linked to desired outcomes of college and what institutions do to induce students to participate in these activities‖ (p. 623). To be specific, engagement in this study will be investigated in terms of the time and effort teachers and students devote to achieve the expected learning outcomes as indicated by students' roles and contribution in classroom interactions, student engagement is associated with experimental and traditional measures of academic performance, whether the relationships between engagement and academic performance are conditional, and whether institutions differ in terms of their ability to convert student engagement into academic performance; Crook and Mitchell (2012) investigated how SLE was realized in various learning spaces; Angelaina and Jimoyiannis (2012) investigated students' participation and learning presence in an educational blog implemented as a crossthematic inquiry activity; Boss, Angell, and Tewell (2015) assessed the success of Amazing Library Race in developing SLE in library orientation sessions; and Tan and Hew (2016) examined how the use of meaningful gamification affects student learning, engagement, and affective outcomes in a short, 3-day blended learning research methods class using a combination of experimental and qualitative research methods. SLE, as indicated earlier, has been studied in different ways and perspectives.…”
Section: Introductionmentioning
confidence: 99%
“…For the purpose of this study, following Kuh (2009), engagement is considered to represent -the time and effort students devote to activities that are empirically linked to desired outcomes of college and what institutions do to induce students to participate in these activities‖ (p. 623). To be specific, engagement in this study will be investigated in terms of the time and effort teachers and students devote to achieve the expected learning outcomes as indicated by students' roles and contribution in classroom interactions, student engagement is associated with experimental and traditional measures of academic performance, whether the relationships between engagement and academic performance are conditional, and whether institutions differ in terms of their ability to convert student engagement into academic performance; Crook and Mitchell (2012) investigated how SLE was realized in various learning spaces; Angelaina and Jimoyiannis (2012) investigated students' participation and learning presence in an educational blog implemented as a crossthematic inquiry activity; Boss, Angell, and Tewell (2015) assessed the success of Amazing Library Race in developing SLE in library orientation sessions; and Tan and Hew (2016) examined how the use of meaningful gamification affects student learning, engagement, and affective outcomes in a short, 3-day blended learning research methods class using a combination of experimental and qualitative research methods. SLE, as indicated earlier, has been studied in different ways and perspectives.…”
Section: Introductionmentioning
confidence: 99%
“…It also showed that using game mechanics had a positive impact on students' motivation to engage in more challenging activities during the course. In the present study, mental gamification also influenced thestudents' interaction in the classroom [52].…”
Section: Discussionmentioning
confidence: 49%
“…Únicamente se obtienen resultados cuando se emplean los términos en inglés, "gamification" AND "blended learning". Se consideraron 49 publicaciones, 23 de Web of Science (WOS) y 26 de Scopus, siguiendo la estrategia de búsqueda descrita, de las que 15 publicaciones pertenecientes a revistas científicas y actas de conferencias indexados en ambas bases de datos se encuentran reiteradas (Arnab, Bhakta, Merry, Smith, Star, y Duncan, 2016;Arnab, Tombs, Duncan, Smith, y Star, 2015;Baker, Bujak y DeMillo, 2012;Berkling, 2015;Dagnino, Antonaci, Ott, Lavagnino, Bellotti, Berta, y De Gloria, 2015;Dichev y Dicheva, 2013;Friess, et al, 2015;Hew, Huang, Chu, y Chiu, 2016;Lennon, Abbott y McIntosh, 2015;Lückemeyer, 2015;Mozelius, Collin y Olsson, 2015;Priego y Peralta, 2013;Tan y Hew, 2016;Velázquez, 2015). Por lo tanto, la muestra de este estudio ha constado de 34 publicaciones.…”
Section: Metodologíaunclassified